Structural homogenization among ASEAN-5 economies - Chong, Choy Yoke; Habibullah, Muzafar Shah (2014)
A successful economic integration shall result to real income convergence within a region. It helps the poorer countries within the region to catch-up with the richer counterparts. Hence, poorer countries shall undergo extensive development and move from an agriculture-dominant economy towards industrial and then the service-dominant economy according to the famous three-sector hypothesis. Therefore, these countries within the region tend to have their economic structure become more similar over time and it is defined as structural homogenization (convergence). Such convergence in productive structures is also essential for a sustainable region in order to overcome the asymmetry of shocks. Empirical studies showed that ASEAN-5 has achieved certain degree of income convergence over the years. However, limited studies focused on the adjustment of sector structures among ASEAN-5 countries. Therefore, this paper would like to perform a more comprehensive convergence study among ASEAN-5 countries in terms of homogenization in their production structures. Output shares of five categorized sectors over 1970 to 2012 was examined using heterogeneity index proposed by Palan and Schmiedeberg (2010). Our results revealed that the heterogeneity index has decreased over time implying that ASEAN-5 has experienced convergence in their production structures as well. Hence, this finding provides new evidence of further real convergence among ASEAN-5 countries that strengthen the sustainability as a successful region.